Activation of the alpha 7 nicotinic acetylcholine receptor by GTS-21 mitigates contrast nephropathy in a rat model. - YEGEN, BERRAK (My University, 2024)
Introduction: Contrast nephropathy (CN) is characterized by oxidative stress, vasoconstriction, tubular toxicity and hypoxia of the renal medulla. We aimed to test the therapeutic effects of an α7 nicotinic acetylcholine receptor (nAChR) agonist, GTS-21, in an experimental CN model. Methods: Male Sprague‒Dawley rats (n=40) were divided into 4 groups: saline-treated control, GTS-21-treated control, contrast, and GTS-21-treated contrast groups. Starting on the 1st day, GTS-21 (4 mg/kg, intraperitoneally) or saline was administered twice a day for 3 days. CN was induced on the second day by intravenous injection of indomethacin (10 mg/kg), L-NAME (10 mg/kg), and a contrast agent with high osmolarity (6 ml/kg; Urografin 76%). At the 72nd hour, blood and kidney samples were obtained for the determination of biochemical, histological, and gene expression parameters. Results: Compared to those in control rats, the elevated serum BUN level in the contrast group decreased with GTS-21 treatment, while H&E staining and TUNEL assays showed that contrast-induced renal injury was improved by GTS-21. Moreover, GTS-21 treatment in the CN also increased the antioxidant glutathione level. In the contrast group, a significant increase in IL-6 expression and a decrease in TGF-β expression were observed; however, GTS21 treatment decreased IL-6 expression and increased TGF-β expression. Conclusion: GTS-21 significantly alleviated renal injury parameters through antioxidant, anti-inflammatory, and antiapoptotic mechanisms in the CN model.
Keywords: Contrast nephropathy; GTS-21; alpha 7 nicotinic acetylcholine receptor; cholinergic anti-inflammatory pathway; oxidative stress